Optical spectroscopy of charge transfer transitions in multiferroic manganites, ferrites, and related insulators (Review Article) - Moskvin, A.S.; Pisarev, R.V. (Физика низких температур, 2010)
We review results of theoretical and experimental studies of charge transfer (CT) transitions in multiferroic manganites, ferrites, and related insulators. Starting with a simple cluster model approach we address both onecenter p–d and two-center d–d CT transitions, their polarization properties, the role played by structural parameters, orbital mixing, and spin degree of freedom. We analyze optical ellipsometry data in the spectral range of 0.6–5.8 eV in perovskite and hexagonal rare-earth manganites RMnO₃ and in orthorhombic manganites RMn₂O₅. We discuss two groups of iron oxides where Fe³⁺ ions occupy either only octahedral positions (BiFeO₃, orhoferrites RFeO₃ et al.) and materials with Fe³⁺ ions both in octahedral and tetrahedral positions (hematite α-Fe₂O₃, garnets RFe₅O₁₂, lithium ferrite LiFe₅O₈, Ca₂Fe₂O₅ et al.).